Political obligation [ a critical introduction - Knowles, Dudley (Routledge contemporary political philosophy, 2010)
Political obligation is concerned with the clash between the individual's claim to self-governance and the right of the state to claim obedience. It is a central and ancient problem in political philosophy. The author frames the problem of obligation in terms of the duties citizens have to the state and each other